The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1186/2041-9139-3-17
|View full text |Cite
|
Sign up to set email alerts
|

Development of an embryonic skeletogenic mesenchyme lineage in a sea cucumber reveals the trajectory of change for the evolution of novel structures in echinoderms

Abstract: BackgroundThe mechanisms by which the conserved genetic “toolkit” for development generates phenotypic disparity across metazoans is poorly understood. Echinoderm larvae provide a great resource for understanding how developmental novelty arises. The sea urchin pluteus larva is dramatically different from basal echinoderm larval types, which include the auricularia-type larva of its sister taxon, the sea cucumbers, and the sea star bipinnaria larva. In particular, the pluteus has a mesodermally-derived larval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
104
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(110 citation statements)
references
References 47 publications
5
104
0
Order By: Relevance
“…Thus, in the early development of echinoids, the regulation of gcm changed markedly and at numerous nodes of the GRN; however, gcm still demarcates NSM polarity, which appears to be an echinoid novelty. This hypothesis is supported by the observation that no significant polarity occurs during embryonic mesodermal specification of asteroids, ophiuroids, and holothuroids (95)(96)(97). Thus, polarization of gcm and ese is a derived feature of echinoids that likely first appeared at least 268 mya, and the mechanism of NSM segregation via Nodal/SMAD signaling is likely conserved since that time (Fig.…”
Section: Divergent Regulatory Linkages In the Evolution Of Echinoid Esupporting
confidence: 58%
“…Thus, in the early development of echinoids, the regulation of gcm changed markedly and at numerous nodes of the GRN; however, gcm still demarcates NSM polarity, which appears to be an echinoid novelty. This hypothesis is supported by the observation that no significant polarity occurs during embryonic mesodermal specification of asteroids, ophiuroids, and holothuroids (95)(96)(97). Thus, polarization of gcm and ese is a derived feature of echinoids that likely first appeared at least 268 mya, and the mechanism of NSM segregation via Nodal/SMAD signaling is likely conserved since that time (Fig.…”
Section: Divergent Regulatory Linkages In the Evolution Of Echinoid Esupporting
confidence: 58%
“…However, differences in skeleton formation and embryonic territories specification in this group are the result of evolutionary changes, which include gene duplications, protein function diversification, and genes co‐opted to different functions (Dylus et al., 2016; Hinman & Davidson, 2007; Hinman, Nguyen, Cameron, et al., 2003; McCauley et al., 2010, 2012). Here, comparisons of early developmental transcriptomes of echinoderms revealed several proteins/genes that are highly conserved among sea urchins, sea cucumbers, and brittle stars (Figure 2b,c).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the differences in larval development in this group (e.g., pluteus‐, bipinnaria‐, and auricularia‐like larvae), comparisons of their GRN architectures have detected highly conserved orthologous regulatory genes among the extant echinoderm classes (Hinman & Davidson, 2003a,b; Hinman, Nguyen, Cameron, & Davidson, 2003; Hinman, Nguyen, & Davidson, 2003). While the network logic employed is the same in these organisms, the transcription factors underlying certain functions have been the subject of evolutionary change, resulting in gene duplications, protein function diversification, and regulatory genes co‐opted to different functions (Dylus et al., 2016; Hinman & Davidson, 2007; Hinman, Nguyen, Cameron, et al., 2003; McCauley, Weideman, & Hinman, 2010; McCauley, Wright, Exner, Kitazawa, & Hinman, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…The holothurian P. parvimensis was developed as an experimental developmental system only recently, once improved methods for spawning animals were established (38,39). Those earlier studies revealed that P. parvimensis has an alx1-expressing PMC-like cell lineage that produces a small larval spicule.…”
Section: Resultsmentioning
confidence: 99%
“…Those earlier studies revealed that P. parvimensis has an alx1-expressing PMC-like cell lineage that produces a small larval spicule. This lineage arises in the vegetal pole, and, before ingression, alx1 is coexpressed with holothurian tbr, ets1, and erythroblast transformation specific ets-related gene (erg) orthologs (38). The expression of hesc, and indeed any earlier mechanisms that might lead to the specification of this lineage at the vegetal pole of P. parvimensis, were not determined, however.…”
Section: Resultsmentioning
confidence: 99%